In Vitro Antimalarial Activity and Toxicity of Helianthus annuus L. Leaf Extract against Plasmodium falciparum - Nuriha Marangoh; Suciati Suciati; Wiwied Ekasari (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2021)
Background: Malaria is one of the public health problems in Indonesia. The morbidity rate is still quite high, especially in the eastern part of Indonesia. Objective: This study aimed to determine the inhibitory activity of the leaf extracts of Helianthus annuus L. against Plasmodium falciparum strain 3D7 as well as the cytotoxicity of the extracts. Methods: The leaves of H. annuus were extracted by the maceration method with n-hexane, chloroform, and ethanol 96% to increase polarity. The antimalarial assay was performed by using Trager and Jensen method, and the cytotoxicity test was carried out by the MTT method. Results: The results of antimalarial study showed that the chloroform extract had IC50 value of 0.002 µg/mL and CC50value of 138.03 µg/mL, 96% ethanol extract had an IC50 value of 0.02 µg/mL and CC50 value of 617.81 µg/mL, and n-hexane extract had an IC50 value of 1.29 µg/mL and CC50 value of 104.89 µg/mL. The selectivity index (SI) values of the chloroform, ethanolic, and n-hexane extracts were calculated and obtained 69,015.00, 30,890.50, and 81.31, respectively. Conclusion:  To conclude, the chloroform extract of H. annuus L. leaf gave strong antimalarial activity against P. falciparum strain 3D7 without any cytotoxicity; therefore, H. annuus L. leaf can be a good candidate for the development of an antimalarial drug.